Mixed plantation and insect herbivory across a harvesting gradient in North Patagonian forest - Nacif, Marcos; Garibaldi, Lucas Alejandro; Quintero, Carolina
Sustainable forest management should optimize tree productivity and biodiversity conservation. However, it is unknown how different tree species and their associated herbivores respond to a gradient of forest extraction or if exists an optimum harvesting level for plant performance and herbivore guild diversity. In an experimental management program in Patagonian shrublands, were planted Austrocedrus chilensis, Nothofagus alpina, N. pumilio, N. antarctica, N. dombeyi and N. obliqua, in plots with different harvesting intensities. Plant survival, growth and leaf damage of herbivore guilds were measured. Mixed model effects were used. The plants survived more and grew better at intermediate harvesting intensities. Two groups of plants presented similar consumption patterns, coincidentally with their phylogenetic proximity. These responses were obtained with different guilds. N. obliqua and N. alpina were more consumed at intermediate harvesting intensities, and N. pumilio, N. antarctica and N. dombeyi were more consumed at lower harvesting intensities. A non deciduous species was the less consumed (N. dombeyi). Diversity patterns are similar to herbivory rates (not for N. dombeyi in the second year). Intermediate harvesting is optimal for plant performance and herbivore guild diversity. In a productive forest scenario, harvesting is necessary, also ensure herbivore guild diversity. Fil: Nacif, Marcos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural. - Universidad Nacional de Rio Negro. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural; Argentina Fil: Garibaldi, Lucas Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural. - Universidad Nacional de Rio Negro. Instituto de ...